A Universal Approach to Molecular Identification of Rumen Fluke Species Across Hosts, Continents, and Sample Types - Mitchell, Gillian; Zadoks, Ruth N.; Skuce, Philip J. (Frontiers in Veterinary Science, 2021)
Rumen fluke are parasitic trematodes that affect domestic and wild ruminants across a wide range of countries and habitats. There are 6 major genera of rumen fluke and over 70 recognized species. Accurate species identification is important to investigate the epidemiology, pathophysiology and economic impact of rumen fluke species but paramphistomes and amphistomes are morphologically plastic, which has resulted in numerous instances of misclassification. Here, we present a universal approach to molecular identification of rumen fluke species, including different life cycle stages (eggs, juvenile and mature fluke) and sample preservation methods (fresh, ethanol- or formalin fixed, and paraffin-wax embedded). Among 387 specimens from 173 animals belonging to 10 host species and originating from 14 countries on 5 continents, 10 rumen fluke species were identified based on ITS-2 intergenic space sequencing, including members of the genera Calicophoron, Cotylophoron, Fischeroedius, Gastrothylax, Orthocoelium and Paramphistomum. Pairwise comparison of ITS-2 sequences from this study and Genbank showed > 98.5% homology for 80% of intra-species comparisons and < 98.5% homology for 97% of inter-species comparisons, suggesting that some sequence data may have been entered into public repositories with incorrect species attribution based on morphological analysis. We propose that ITS-2 sequencing could be used as a universal tool for rumen fluke identification across host and parasite species from diverse technical and geographical origins and form the basis of an international reference database for accurate species identification.